CLIMATE CHANGE: THE POLITICS AND CHALLENGES IN PERSPECTIVE OF THE INTERNATIONAL ENVIRONMENTAL LAWS - Abbas Sheer; Li Shouping; Fatima Sidra (Journal of Liberty and International Affairs, 2019)
This article consists of five major parts. It includes the analysis of politics and international cooperation on climate change and the legal environmental scenario and implementation, trends and litigation concerns faced by climate change. The Paris Agreement of Climate Change (2015) and Sustainable Development Goals (SDGs) of the United Nation are the two main players at the global level to target greenhouse gas emissions as a voluntary framework. These guiding principles relating to the environment for sustainable development are evolving over time and did not shape as customary law. The ultimate solution lies in understanding the problem intensity through growing scientific facts about the impacts of climate change.